Preparation and structural-optical characterization of dip-coated nanostructured Co-doped ZnO dilute magnetic oxide thin films - Valério, L. R.; Mamani, N. C.; De Zevallos, A. O.; Mesquita, A. [UNESP]; Bernardi, M. I.B.; Doriguetto, A. C.; De Carvalho, H. B. (Royal Society of Chemistry (RSC), 2017)
ZnO-based materials are one of the most studied systems. Their applicability spans over several research areas and industries, like optoelectronics, catalysis and spintronics. Here we demonstrate the feasibility to prepare Co-doped ZnO thin films (Zn1−xCoxO, with x = 0; 0.01; 0.03 and 0.05) deposited by the dip-coating technique, a very simple and a low-cost process. We focus the structural and the optical characterization in the context of dilute magnetic materials. Detailed analyses were carried out to investigate alternative sources of ferromagnetism, such as secondary phases and nanocrystals embedded in the nanostructured thin films. Conjugating different techniques, we confirmed the Zn replacement by Co ions in the ZnO wurtzite structure with no secondary phases up to x = 0.05. It was further observed that the major structural defects in the films are oxygen vacancies (VO) and zinc interstices (Zni), and that the relative densities of these defects increase with the increase in Co concentration, which promotes the studied thin films to candidates to present room temperature ferromagnetism.